A Historical Booklet on Horse Racing: A Team Sport of Human and Animal - Genc, Savas Volkan; Ural, Selçuk; Özgür, Atilla (Progress in Nutrition, 2022)
Study Objectives: A historical book on horse racing, a sport that humans and horses do together, was reviewed. It was aimed to contribute to the history of sports and veterinary. Methods: In this study, which was designed as document analysis, one of the qualitative research patterns, a historical booklet on horse racing and horse breeding was examined. Results: The book contains information on the history of horse races in the world and Turkey, horse breeds, racing rules, horse care, and nutrition. There is also information on the walking of the horses, the types of running-race, what the jockeys should do, and the love of horses in the Turks. The importance of horses in the Islamic world is explained. Folkloric information about the horse is also given. Conclusion: In this context, the booklet can be considered as an important scientific and cultural work for the history of Turkish veterinary medicine and Turkish sports history.